OR07-2 Elucidating The Mechanisms Of Action Of Mkrn3 In A Novel Mouse Model Of Delayed Puberty. - Roberts, Stephanie (J Endocr Soc, 2019)
Makorin Ring Finger Protein 3 (MKRN3) is an important neuroendocrine player in the control of pubertal timing. Loss-of-function mutations in MKRN3 are the most common genetic cause of central precocious puberty. Mice have high levels of hypothalamic Mkrn3 expression in the juvenile period, which rapidly decline peripubertally and are low in adulthood, consistent with a role of Mkrn3 as an inhibitor of pubertal onset. Its protein structure includes an E3 ubiquitin ligase domain, suggesting that it may act by targeting proteins for degradation. In this study, we explored the mechanisms of action of Mkrn3 in a novel rodent model of delayed puberty. Female mice that received bilateral intracerebroventricular injections at postnatal day (PND) 1 with recombinant virus expressing Mkrn3 had delayed vaginal opening and first estrus, compared to control-virus injected animals, with subsequent normal cyclicity and fertility. Interestingly, male mice did not exhibit delayed puberty onset, determined by preputial separation, following Mkrn3 overexpression through the same paradigm. There was no effect of Mkrn3 overexpression on mean body weight in either males or females between PND 21 and PND 60. Mkrn3 mRNA levels were increased in the mediobasal hypothalamus and in the preoptic area at PND 28 in both sexes and at PND 60 in males (females not collected) compared to control-virus injected mice. Mkrn3 protein levels were also increased compared to control-virus injected animals in the mediobasal hypothalamus of female mice at PND 28. Surprisingly, Kiss1, Tac2, and Pdyn mRNA levels were increased in the mediobasal hypothalamus in females at PND 28 and in males at PND 60 following Mkrn3 overexpression, compared to controls. Kiss1r, Tac1, Tacr1, Dlk1, Kcnk9 and Lin28b mRNA levels in the mediobasal hypothalamus were not affected by Mkrn3 overexpression. There was no compensatory change in Mkrn1 or Mkrn2 mRNA expression. In the preoptic area, Gnrh1 mRNA was not affected, and in the pituitary, Lhb, Fshb, and Gnrhr mRNA levels were not altered in the setting of Mkrn3 overexpression. Cumulatively, these data suggest that Mkrn3 may act downstream of Kiss1 mRNA, potentially by acting as an E3 ligase as its structure suggests; with the resultant downregulation of the pituitary-gonadal axis leading to subsequent activation of KNDy neurons because of reduced sex steroid negative feedback. A sex difference in the pubertal phenotype in response to Mkrn3 overexpression was observed, suggesting that Mkrn3 may have a greater impact in females than males. The results of this study also suggest that persistent expression of MKRN3 may lead to the phenotype of constitutional delay of puberty in children. In conclusion, this model implicates MKRN3 as a contributor to delaying the onset of puberty in addition to its well-established role in central precocious puberty.